Genetic Alterations in Barrett Esophagus and Adenocarcinomas of the Esophagus and Esophagogastric Junction Region - Wu, Tsung-Teh (American Society for Investigative Pathology, 1998)
The incidence of esophageal adenocarcinoma has increased markedly in the past two decades, but the genetic alterations in this cancer and its precursor, Barrett mucosa, have not been characterized extensively. DNA replication errors and allelic losses of chromosomes 17p, 18q, and 5q were studied in 36 resected adenocarcinomas arising in the esophagus and esophagogastric junction, 56 Barrett adenocarcinomas, and 11 dysplasias in Barrett esophagus. The results were compared with clinical and pathological characteristics, including patient survival. Replication error positive cancer was rare (5.4%) in esophageal adenocarcinomas and was not found in Barrett mucosa. There was an increase in the prevalence of chromosomal losses in the Barrett mucosa–columnar dysplasia–adenocarcinoma sequence: 17p loss occurred in 14% of Barrett mucosae, 42% of low-grade dysplasias, 79% of high-grade dysplasias, and 75% of adenocarcinomas, respectively; loss of 18q in 32%, 42%, 73%, and 69%; and loss of 5q in 10%, 21%, 27%, and 46%. Clinical stage was a very strong prognostic factor for survival, and adenocarcinomas with allelic loss of both 17p and 18q had worse survival than cancers with no or one allelic loss (P = 0.002). Our results indicate that accumulation of genetic alterations follows the dysplasia–adenocarcinoma sequence in the esophagus and that losses of 18q and 17p occur earlier than 5q loss. Allelic loss of both 17p and 18q in esophageal adenocarcinoma identifies patients with poor prognosis.